Mental health of children and youth – examples of actions in the area of prevention and mental health promotion in Polish schools - Czarnecka, Martyna (Forum Pedagogiczne, 2020)
The percentage of children and youth in Poland suffering from mental health disorders is significant. Studies and numerous reports on mental health problems in children and adolescents indicate that in recent years the depression has particularly affected people under 18 years of age. WHO data also emphasizes that adolescent suicide is the third cause of death in this age group. The factors determining mental health can be divided into biological and psychosocial. They depend on individual experiences with their families, peers, or schools, as well as on their genetic equipment and brain functions. The mental health situation of children and adolescents in Poland prompted doctors, psychologists, scientific communities, teachers and educators on the one hand to search, analyze and determine the causes of the problems and take action, on the other, to improve the psychophysical condition of young people. The protection of mental health of children and youth in Poland, prevention and promotion of health are recognized as a priority in the health protection policy.